Mistletoe viscin: a hygro- and mechano-responsive cellulose-based adhesive for diverse material applications. Issue 1 (16th March 2022) - Horbelt, Nils; Fratzl, Peter; Harrington, Matthew J
Abstract: Mistletoe viscin is a natural cellulosic adhesive consisting of hierarchically organized cellulose microfibrils (CMFs) surrounded by a humidity-responsive matrix that enables mechanical drawing into stiff and sticky fibers. Here, we explored the processability and adhesive capacity of viscin and demonstrated its potential as a source material for various material applications, as well as a source for bioinspired design. Specifically, we revealed that viscin fibers exhibit humidity-activated self-adhesive properties that enable "contact welding" into complex 2D and 3D architectures under ambient conditions. We additionally discovered that viscin can be processed into stiff and transparent free-standing films via biaxial stretching in the hydrated state, followed by drying, whereby CMFs align along local stress fields. Furthermore, we determined that viscin adheres strongly to both synthetic materials (metals, plastics, and glass) and biological tissues, such as skin and cartilage. In particular, skin adhesion makes viscin a compelling candidate as a wound sealant, as we further demonstrate. These findings highlight the enormous potential of this hygro- and mechano-responsive fiber-reinforced adhesive for bioinspired and biomedical applications.